Indicators for monitoring and management of coastal Program evaluation: The Orla Project Fundão - Ramos, Aparecida Demoner; Sarmento, Robson (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The degradation and the wear-out of marine and coastal resources, demonstrate the need of giving to the Coast Management programs an integrated focus. The integrated management is a process that puts together the managers and the communities to elaborate and execute programs and projects in search of sustainability for costal and marine ecosystems. The objective of this work is to present a group of environmental, social-economic and institutional indicators having as a goal to quantify, monitor, and evaluate the actions to be developed in the Integrated Coastal Management programs. As criteria to be used for the definitions of the indicators were: i) the problems identified as priority in coastal cities ii) analysis of the different scenarios of the city, state and federal politics related to coastal management iii) present characteristics of being an easy indicators for measurement, centered in practical, clear and easy to understand and to communicate; and vi) to be relevant for the objectives of the Programs and Projects of integrated management of the Fundão coastline – Project Orla. The joint application of the indicators allowed the comprehension of the factors that generate pressure to the environment, the state and the dependency relations among the coastal systems. The usage of these indicators to quantify, monitor and evaluate the implementation of Project Orla in the diverse conditions and environmental, socialeconomic and institutional scenarios must allow the decisions taking and to determine interventions, reaching the necessary goals to the sustainability of the occupation and usage of marine and coastal ecosystems.